Severe Dyspnea Is an Independent Predictor of Readmission or Death in COPD Patients Surviving Acute Hypercapnic Respiratory Failure in the ICU - Dupuis-Lozeron, Elise; Soccal, Paola M.; Janssens, Jean-Paul; Similowski, Thomas; Adler, Dan (Frontiers in Medicine, 2018)
Background: Predicting outcome after index admission in the ICU for COPD-related acute hypercapnic respiratory failure (AHRF) is difficult. Simple tools to stratify this risk and to promote interventions to mitigate it are needed. Aim: To prospectively evaluate the ability of severe dyspnea (NYHAIII-IV) to predict hospital readmission or death in COPD patients surviving AHRF in the ICU. Methods: 50 consecutive COPD patients were recruited from a larger cohort of patients (n=78) surviving AHRF in the ICU. All predictive variables were collected within 15 days after resolution of acute respiratory failure before hospital discharge. COPD was diagnosed by spirometry. Heart failure was diagnosed with clinical rules and echocardiography. NYHA was measured upon hospital discharge. Hospital readmission and death were recorded at regular intervals for 3 months. Results: 21/50 (42%) COPD patients died or were readmitted to the hospital during the observation period: 12 out of the 20 NYHA III-IV patients (60%) and 8 out of the 28 NYHA I-II patients (29%). NYHA III-IV was associated with risk of readmission or death (univariate HR: 2.73, IC95: 1.11-6.69, p=0.028). After controlling for age, FEV1, heart failure and BMI, NYHA III-IV remained associated with readmission or death (multivariate HR: 2.71, IC95: 1.06-6.93, p=0.038). Conclusions: Our findings suggest that severe dyspnea measured upon hospital discharge in COPD patients surviving AHRF can stratify patient’s risk of 3-month readmission or death.